Electrocardiographic, echocardiographic, and indirect blood pressure evaluation in dogs subjected to different sedation protocols - Cardoso,Helena Mondardo (2016)
ABSTRACT: The present study aimed to evaluate the effects of different sedation protocols on blood pressure and echocardiographic and electrocardiographic parameters in dogs. In total, 24 male mixed-breed dogs with a mean weight of 9.87±3.0kg were used.Animals were randomly divided into four groups (n=6), which were subjected to sedation using the following protocols: acepromazine (0.05mgkg-1) and butorphanol (0.3mgkg-1) (AB); acepromazine (0.05mgkg-1)and methadone (0.5mgkg-1) (AM); acepromazine (0.03mgkg-1), methadone (0.5mgkg-1), and midazolam (0.3mgkg-1)(MAM); and methadone only (0.5mgkg-1) (M). Indirect blood pressure (BP) measurements and computerized electrocardiography (ECG) and echocardiography (ECO) were performed immediately before the application of the sedation protocol (baseline), and the same evaluations were repeated after 15 minutes. BP decreased in groups AB, MAM, and AM compared to baseline values. Electrocardiographic measurements showed decreased heart rates (HRs) after sedation in all groups, and bradycardia was observed after sedation in two dogs from group M and one animal from group AM. The P-wave duration increased after sedation in groups AM and M. After sedation, no changes in cardiac dimensions were revealed byECO.Fractional shortening (FS) decreased after sedation in the AM group, and dogs from group AB exhibited a smaller decrease in FS compared with the other groups. The cardiac index (CI) was lower in groups AM and M than in the other groups. Animals from group AB were less resistant to examination and exhibited the most favorable sedation scores. It was concluded that the combination of acepromazine and butorphanol was the best sedation protocol for performing echocardiogram measurementsbecause dogs were less resistant to examinations and echocardiographic parameters of FS and CI remained stable.